2006
DOI: 10.1007/s10888-006-9030-z
|View full text |Cite
|
Sign up to set email alerts
|

The Luxembourg Wealth Study – A cross-country comparable database for household wealth research

Abstract: household wealth, household portfolios, distribution of net worth, international comparative data sources,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 3 publications
(1 reference statement)
3
50
0
3
Order By: Relevance
“…Differences in welfare regimes and the emphasis these regimes put on the magnitude and generosity of publicly provided old-age insurance systems call for the consideration of pension entitlements in comparative wealth studies, for example the analyses based on the Luxembourg Wealth Study (LWS, see Sierminska et al 2006). While net worth can be successfully collected by means of survey data, the knowledge of pension entitlements on behalf of respondents is often limited.…”
mentioning
confidence: 99%
“…Differences in welfare regimes and the emphasis these regimes put on the magnitude and generosity of publicly provided old-age insurance systems call for the consideration of pension entitlements in comparative wealth studies, for example the analyses based on the Luxembourg Wealth Study (LWS, see Sierminska et al 2006). While net worth can be successfully collected by means of survey data, the knowledge of pension entitlements on behalf of respondents is often limited.…”
mentioning
confidence: 99%
“…However, as Figure 4 shows, signi…cant improvements in data availability are not con…ned to developing countries. A renewed interest in the …ne detail of the income distribution among the seriously rich has led to the synthesis of data from tax authorities that has added a new perspective to international comparisons Piketty (2007); new work making available micro-data on wealth will also enhance understanding of what is going on in the upper tail of the income distribution (Sierminska et al 2006). …”
Section: Welfare Economics and Distributionmentioning
confidence: 99%
“…At the time of data collection, all of these countries were experiencing low unemployment and positive GDP growth (Table 1) The data contain detailed information on multiple income sources and financial and nonfinancial assets and debts. On the basis of this detailed information, we use the conceptual framework developed by the Luxembourg Wealth Study (described in Sierminska et al (2006)) for creating harmonized variables of net worth (total assets: financial assets, principal residence, investment real estate and business equity minus liabilities: mortgages and non-housing debt) and income. Each of the wealth variables have been bottom and top coded at their 1% and 99% levels to stop outliers from over-influencing our results and monetary variables have been converted to 2007 Euros using PPP and price indices.…”
Section: Datamentioning
confidence: 99%
“…Our focus is on the main assets and liabilities held by households; financial assets, main residence, investment real estate and debt, with a focus on mortgages and non-housing debt. 2 Past research suggests a large role for institutions in explaining cross-national differences in portfolios. Christelis et al (2012) find that characteristics play a small or negligible role in generating observed international differences for households 50 years and over.…”
Section: Introductionmentioning
confidence: 99%